Digital assessment and intervention strategies for teachers' occupational health during the COVID-19 pandemic - Halyna M. Meshko; Oleksandr I. Meshko; Iryna M. Trubavina; Nadia M. Drobyk; Vasil V. Grubinko; Nadiia I. Bilyk; Nataliia V. Habrusieva (CTE Workshop Proceedings)
This study investigates teachers' occupational health challenges and intervention strategies during the COVID-19 pandemic in Ukraine. Using digital assessment methods via Google Forms, we surveyed 322 teachers from urban (62.7%) and rural (37.3%) schools to evaluate occupational health indicators before and during quarantine periods. Results reveal significant deterioration in teachers' psychological well-being, emotional regulation, and professional satisfaction during pandemic-related restrictions. Notably, teachers with over 10 years of experience showed more pronounced negative health impacts, as did those working in rural settings with limited digital infrastructure. The study identified critical needs for psychological support, revealing that 42% of female teachers and 25% of male teachers required professional health-related assistance during quarantine. Based on these findings, we developed a comprehensive framework for the Centre of Pedagogical Consulting that offers targeted digital intervention strategies, including webinars, online training, and remote psychological support services. This research demonstrates the essential role of digital technologies in both assessing and addressing teachers' occupational health challenges during educational disruptions, providing a model for integrating remote support services into educational systems facing similar crises.